Coordination dynamics in horse-rider dyads - Wolframm, I. A.; Bosga, J.; Meulenbroek, R. G. J. (Human Movement Science, 2013)
The sport of equestrianism is defined through close horse-rider interaction. However, no consistent baseline parameters currently exist describing the coordination dynamics of horse-rider movement across different equine gaits. The study aims to employ accelerometers to investigate and describe patterns of motor coordination between horse and rider across the equine gaits of walk, rising trot, sitting trot and canter. Eighteen female (N = 18; mean age ± SD: 37.57 ± 13.04) Dutch horse-rider combinations were recruited to participate in the study. Horse-rider coordination was recorded using two tri-axial wireless accelerometers during a standard ridden protocol. Multiple measures of horse-rider coordination were calculated to investigate the relationship between the horse and rider, while the unpredictability of the acceleration-time series of the horse and rider during task performance were determined separately by means of approximate entropy analysis. The kinematic variables of horse-rider correlation, mean relative phase, mean standard deviation of the relative phase, approximate entropy rider, approximate entropy horse and spectral edge frequency at 95% of the power in the 0-10 Hz frequency band were examined using multiple correlational analyses and multivariate analysis of variance (MANOVA). Findings showed significantly different coordination dynamics between equine gaits, with the gait of canter allowing for the highest levels of horse-rider synchronicity. It may be concluded that accelerometers are a valuable tool to map distinct coordination patterns of horse-rider combinations